Spectral Measurements Improvement Technique for IEEE 802.15.4zUltra Wideband Devices - Tsaturyan, Grigor
The adoption of IEEE 802.15.4z ultra wideband (UWB) technology is rapidly increasing due to its capabilities in delivering precise ranging, low latency, and interference resistant communication for indoor navigation and centimeter level distance determination applications. This growing usage has intensified the demand for accurate testing and measuring methods, which are critical for minimizing interference and ensuring reliable performance. Traditionally, spectral measurements have been conducted using a single signal analyzer, where the noise introduced by the analyzer itself can limit the accuracy of the results. In this article, a novel approach for spectral measurements of 802.15.4z UWB waveforms is proposed, utilizing two synchronized signal analyzers combined with a cross correlation technique. By cross correlating the received signals from both analyzers, the impact of noise is effectively mitigated, leading to a reduction in the noise of the measurement system. This approach enhances the precision of spectral measurements, ensuring that the spectral characteristics of the UWB waveform are accurately captured. A comparison of this method with traditional single analyzer techniques is presented.
Keywords: Physics